Unsupervised machine learning based key management in wireless sensor networks - D. Sowmyadevi; I. Shanmugapriya (Measurement: Sensors, 2023)
In distributed sensor applications, the secured infrastructure plays a major role in processing and transmission of data. The data transfer in wireless sensor network (WSN) is equipped security measure that prevents the manipulation of data theft by the attackers. The key management protocol offers secured delivery of messages that includes integrity and authenticity via key generation, key distribution and maintenance. In this paper, we develop a lightweight key management protocol (LKMP) that involves reduced memory consumption and processing power. The study uses machine learning algorithm for key management in WSN, and the machine learning uses unsupervised learning mechanism. The simulation is conducted in network simulator and it is compared with existing state-of-the-art models. The results of simulation shows that the proposed method achieves higher rate of throughput, security and resilience than its predecessors.